Operation -regular spaces, normal spaces with α(γ, γ′)-open sets in topological spaces. (July 2020) - Kalaivani, N; Saravanakumar, D
Abstract: In this paper the α ( γ, γ ′) -regular spaces, α ( γ, γ ′) -normal spaces have been introduced also some of its properties have been studied.